A Comparison of Mepivacaine Versus Lidocaine for Episcleral (Sub-Tenon's) Block for Cataract Surgery in an Ambulatory Setting. Issue 3 (1st May 2006) - Ripart, Jacques; Nouvellon, Emmanuel; Chaumeron, Arnaud; Chanial-Bourgaux, Catherine; Mahamat, Aba
Abstract : Background and Objectives: For eye surgery, motor block is still often requested by the surgeon. For cataract surgery, rapid block resolution allows eyelids to move and allows eye-patch removal. Therefore, short-duration block is useful in early rehabilitation for ambulatory surgery. Lidocaine is classically assumed to have shorter duration than mepivacaine. Therefore, lidocaine alone might be considered as an alternative to mepivacaine. Methods: In this randomized, double-blind study, we compared mepivacaine 2% (n = 22) and lidocaine 2% (n = 25) in 47 patients who received episcleral (sub-Tenon's) block for cataract surgery. Akinesia score was measured 1, 5, 10, and 15 minutes and 1, 2, 4, and 6 hours after the end of injection. Primary outcome was block duration (time from injection to full recovery). Secondary outcomes were time to block onset and best akinesia score for each patient. Complications were recorded. Results: The 2 groups were similar for demographic and anesthetic features. We observed no significant difference between mepivacaine and lidocaine in terms of onset, quality of akinesia, and block duration. One case of ocular hypertonia and 1 case of strabismus were observed in the lidocaine group, which could be imputed to hyaluronidase unavailability during the study period or to increased lidocaine myotoxicity. Conclusions: We found no argument to favor lidocaine over mepivacaine in episcleral (sub-Tenon's) eye block, especially in terms of motor-block duration.